Antimicrobial screening and GC-MS analysis of bioactive compounds from strains of pseudomonas aeruginosa isolated from poultry fecal littered soil in Ibadan, Nigeria. (2019)
The emergence of pathogens exhibiting multiple antibiotic resistance (MDR) is bringing a thwart to available chemotherapeutic agents thus the urgency in the search for bioactive agents that will be effective against the MDR pathogens. This study screened isolates of Pseudomonas aeruginosa from poultry fecal littered soil in two selected locations in northern Ibadan, southwest Nigeria (University of Ibadan Teaching Research Farm and Ayede community) for production of bioactive compounds, evaluated their activities against selected MDR bacteria pathogens and analyzed the crude ethylacetate extract using GC-MS. A total of 178 strains of P. aeruginosa were isolated on cetrimide agar and identified presumptively by standard biochemical test. Primary and secondary screening of the whole cell and cell free supernatant ethylacetate extracts were done by perpendicular streaking and agar-well diffusion methods respectively against selected clinical MDR bacteria pathogens. Five out of the 178 strains of the presumptive P.aeruginosa with excellent antibacterial activity were further confirmed by 16S rRNA amplification and sequencing. Cell free supernatant ethylacetate extracts of two most active strains among the five (denoted with code APC2-1 and APC2-14) were subjected to GC-MS analysis of the metabolites. The five P. aeruginosa strains were identified as P. aeruginosa MR24 strains 1, 2, 3, Pseudomonas sp SD12 and P. aeruginosa Kasamber 1 which were closely related phylogenetically. The bioactive compounds produced by the isolates that were studied had greater activity on Gram positive than Gram negative pathogens. GC-MS analysis revealed a total of 19 different compounds (1-heptadecanamine; 2ethyl-1-hexanamine; 3-butyn-1-ol; Pent-3-enylamine; Pent-4-enylamine; Propane; Acetaldehyde; Ethylene oxide; hydroxyacetonitrile; Bromo-acetonitrile; Azetidine; 2-methyl-Azetidine; Aminocaproic acid; 18nonadecen-1-amine; 5-aminovaleric acid; 2,2-dimethyl-1,3-propanediamine; 1-octadecanamine; 1-octanamine and 2-(3-butynyloxy)tetrahydro-2H-pyran) among which are antibacterial, anticancer, antifibrinolytic, and antimalarial compounds. This study therefore revealed the potentials of Pseudomonas aeruginosa as producers of secondary metabolites of medical and industrial importance. Multidrug resistance is currently on the increase, globally threatening public health and decreasing the efficacy of the antibiotics available currently (WHO, 2017). This therefore, has precipitated the search for novel compounds from natural sources like the environment, beneficial microorganisms, animals and plants from both aquatic and terrestrial habitats with potentials to produce potent antimicrobial agents against the resistant pathogens (Wolfender et al., 2015; Dias et al., 2016). Microbial genome mining is an important tool in the discovery of unculturable organisms and screening of isolates with potential secondary metabolites (Bachmann et al., 2014; Ziemert et al., 2016). With the availability of certain technologies like Ultra-High Performance Liquid Chromatography (UHPLC) and Gas Chromatography and Mass Spectrometry Analysis (GC-MS), an effective separation and identification of different bioactive metabolites from natural products is achievable. Some microorganisms such as bacteria and fungi from ages produce antimicrobials and other bioactive compounds (Butler and Bus, 2006). Pseudomonas spp. are group of Gram-negative bacilli with polar flagella, Gammaproteobacteria and family, Pseudomonadaceae. The species of this genus have a wide array of metabolic diversities capable of colonizing different ecological niches requiring non-specific nutritional requirement for their growth (Meyer et al., 2002). Pseudomonas spp. are known producers of bioactive metabolites such as Phenazine compounds, volatile organic compounds, thioquinolobactin etc. Some of these metabolites have been reported to possess antimicrobial activity, anticancer property, biosurfactant, bio-controlling, bio-pesticide/ bioinsecticide and bioremediation effects, hence its application in pharmaceutical, agricultural, cosmetic, industrial and environmental sector is important (Meyer et al., 2002; Kumar et al., 2016; Gionco et al., 2017). Despite the numerous antibiotics produced from microorganisms most especially the actinomycetes, resistance has taken a